US energy policies and variance in the GCC stock markets - Ben Sita, Bernard (2013)
We investigate the impact of bills about energy policy, introduced and discussed in the US Congress, on the conditional variance process of the five largest Gulf Cooperation Council (GCC) stock markets. Using an augmented asymmetric Generalized AutoRegressive Conditional Heteroskedasticity (GARCH) model, we investigate the hypothesis that public news associated with US energy policy leads to the reversion of the conditional variance process. Our findings are consistent with the information hypothesis. GCC stock variance tends to revert on days when bills are introduced and discussed in the US Congress.